As old as time : a twisted tale - Braswell, Liz (New York : Disney-Hyperion, 2016)
In this reimagining of *Beauty and the Beast*, Belle discovers her mother was the one who cursed the Beast, leading her to uncover shocking truths and face dangerous choices.
"What if Belle's mother cursed the Beast?"--Cover.
Keywords: Beauty and the Beast (Tale) -- Adaptations; Curses -- Fiction; Magic -- Fiction; Princesses -- Fiction; Good and evil -- Fiction; Young adult fiction